Influence of hard segment content and nature on polyurethane/multiwalled carbon nanotube composites - COLEMAN, JONATHAN NESBIT (My University, 2011)
Knowledge of how polyurethanes, PU, complexity affects their derived multiwalled carbon nanotube, MWCNT, composites could shed important clues for preparing future tailored PU/MWCNT elastic, strong and electrically conductive composites. In this regard, hard segment content and nature, along with MWCNT functionalisation, are believed to have great influence on both nanoscale PU/MWCNT self assembling mechanisms and on final composites properties. In this work the effect of PU hard segment content into composites was analysed. According to the results, a preferential interaction of nanotubes with polyurethanes hard segments can be assumed although nanotubes introduction hindered both soft and hard segments crystallisation. In all cases carbon nanotubes percolative network formation seemed to be crucial for obtaining significant reinforcement, being observed at this stage, a reduction of ductility, phenomena which is related to an increase on hard domains interconnections by MWCNT. The hard to soft segment ratio into PU plays a crucial role on determining the stress transfer to MWCNT. In addition, PU hard domains nature has important effect on nanotubes reinforcing character, this fact being related to the different PU intrinsic morphologies as well as different PU-MWCNT interactions.
PUBLISHED
Keywords: Physical chemistry; Nanomaterials; carbon nanotube